Effects of storage time at 32.5oC on amount of Bacillus cereus in UHT milk for school in Chonburi Province - Tongkamsi, Suttitas; Singasa, Kanokwan; Tubtim, Tharinee; Nakbubpa, Kulchai; Chansilpa, Tuota; Kayee, Sirikan (Veterinary Integrative Sciences, 2015)
The objective of this research was to study about the effects of storage time at 32.5 ± 0.63oC on amount of Bacillus cereus in UHT milk. By using the direct plate count method from 74 UHT milk samples, which were collected from schools in Chonburi province between January – August 2013. The results showed that 17 samples (22.97%) were found to be contaminated by B.cereus which the amount of B. cereus was in the range of 3.73 - 5.13 logCFU/mL. Furthermore, dividing UHT milk samples along batches showed no significant (P≤0.05) between storage times and batches with amount of B.cereus. According to these results, it is possibly that other factors could relate to the amount of B.cereus in UHT milk which must be further studies.